Avaliação da produção de citocinas, expressão gênica e análise funcional de células SHED expostas ao LTA bacteriano - Leal, Flávia Martins [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Dental pulp stem cells are promising in endodontics, but before clinical treatment it should be studied to understand its biological properties in response to stimuli such as lipoteichoic acid (LTA). The aim of this study was to evaluate the behavior of Stem cells from Human Exfoliated Deciduous teeth (SHED) exposed to LTA, analyzing cell proliferation and metabolism, alkaline phosphatase activity, calcium deposition, gene expression, cytokines production. SHED cells were treated with LTA, in different concentrations, without and with mineralization induction (MI). Cell metabolism and proliferation were evaluated by XTT and SRB. Alkaline phosphatase activity was performed to indicate mineralization process. Also, calcium deposition was observed qualitatively by alizarin red. Gene expression of DSPP (Dentin Sialophosphoprotein) and DMP-1 (Dentin Matrix Protein-1) was evaluated by PCR (Polymerase Chain Reaction). Cytokines IL-1ß (Interleukin-1ß), IL-6 (Interleukin-6), TNF-α (Tumor Necrosis Factor-α) were detected and quantified by ELISA (Enzyme Linked Immuno Sorbent Assay). Statistical analysis of quantitative tests were performed by ANOVA and Tukey test (p<0,05). Metabolism and cell proliferation increased with time and no differences were observed between groups in each period. In groups without MI, there was an increase in alkaline phosphatase activity of cells exposed to LTA compared to control. Groups with mineralization induction showed more calcium deposition, compared to the groups without MI. After 3 days, cells treated with LTA showed more areas of calcification compared to control, and after periods of 7 and 14 days were similar. All groups tested expressed genes DSPP and DMP-1, being slightly higher in groups with MI. The expression of IL-1ß and TNF-α by cells of the tested groups were similar, and IL-6 concentration was expressive, with differences between groups and time periods. According to the methodology and analysis ...l

Células-tronco da polpa dentária humana são promissoras no tratamento endodôntico, porém antes de utilizá-las clinicamente, deve-se entender suas propriedades biológicas em resposta a estímulos, como o ácido lipoteicóico (LTA) bacteriano. O objetivo deste estudo foi avaliar o comportamento de células SHED (Stem cells from Human Exfoliated Deciduous teeth) após exposição ao LTA bacteriano, verificando os efeitos na proliferação e metabolismo celular, atividade da fosfatase alcalina, deposição de cálcio, expressão de genes associados à mineralização, e liberação de citocinas. Foram utilizadas células SHED tratadas com LTA em diferentes concentrações, sem e com indutores da mineralização (IM). O metabolismo e a proliferação celular foram avaliados pelos ensaios de XTT e SRB. As células foram submetidas a um ensaio enzimático da atividade de fosfatase alcalina, para observação da ativação de processos de mineralização. E foi analisada qualitativamente a presença de deposição de cálcio pelas células pelo ensaio de alizarin vermelho (ARS). A expressão dos genes DSPP (Dentin Sialophosphoprotein) e DMP-1 (Dentin Matrix Protein-1) foi avaliada pela técnica do PCR (Polymerase Chain Reaction). O teste ELISA (Enzyme Linked Immuno Sorbent Assay) foi realizado para detectar e quantificar as citocinas IL-1ß (Interleucina-1ß), IL-6 (Interleucina-6), TNF-α (Fator de Necrose Tumoral-α). Os dados obtidos nos ensaios quantitativos foram analisados estatisticamente por ANOVA complementada pelo teste de Tukey (p<0,05). Foi observado um aumento no metabolismo e proliferação celular com o tempo, não havendo diferenças entre os grupos testados em cada período. Nos grupos sem IM, observou-se um aumento da atividade da fosfatase alcalina das células expostas ao LTA comparados ao controle. Os grupos com indutores de mineralização apresentaram maiores quantidades...
Keywords: Células-tronco; Citocinas; Expressão gênica; Fosfatase alcalina; Polpa dentária; Stem cells